Leaflet thrombosis in transcatheter aortic valve intervention: mechanisms, prevention, and treatment options - Koren, Ofir; Patel, Vivek; Chakravarty, Tarun; Jilaihawi, Hasan; Gupta, Aakriti; Sadri, Shirin; Makkar, Raj R. (Frontiers in Cardiovascular Medicine, 2023)
Transcatheter aortic valve intervention (TAVR) has emerged as a promising alternative to surgical aortic valve replacement (SAVR) for patients with severe aortic stenosis. However, the occurrence of leaflet thrombosis has raised concerns about the long-term durability and outcomes of TAVR. This abstract aims to provide an overview of the mechanisms, prevention strategies, and treatment options for leaflet thrombosis in TAVR.Leaflet thrombosis refers to the formation of blood clots on bioprosthetic valve leaflets, leading to impaired leaflet mobility, early valve degeneration and dysfunction and potential clinical implications.While the mechanisms underlying thrombus formation on the valve leaflets are not fully understood, several factors such as altered blood flow patterns within valve neosinuses, prothrombotic surfaces, and patient-related causes have been implicated. Two distinct entities have been identified: hypo-attenuated leaflet thickening (HALT) and restricted leaflet motion (RELM). Their occurrence appears dynamic over time and related to valve type. Imaging including transesophageal echocardiography and multidetector computed tomography play a crucial role in diagnosis and follow-up of leaflet thrombosis.Preventing leaflet thrombosis requires a comprehensive and tailored approach involving identification of high-risk patients, close monitoring, and antithrombotic therapy. Antithrombotic therapy with dual antiplatelet agents or anticoagulation is commonly employed in TAVR patients, although the optimal regimen is yet to be defined. Novel antithrombotic agents, such as direct oral anticoagulants, are being investigated for their efficacy and safety in preventing leaflet thrombosis. When leaflet thrombosis is detected, treatment options include intensified antithrombotic therapy, valve-in-valve intervention, or balloon valvuloplasty. The long-term outcomes and the impact of leaflet thrombosis on valve durability and patient prognosis are areas of ongoing research.